Statistically designed optimal process conditions for recuperation of protein from rapeseed meal - nil Das Purkayastha, Manashi (J Food Sci Technol, 2014)
This work proposes the exploitation of under-utilized, non-expensive rapeseed press-cake as a source for producing high yield of protein, having superior whiteness and emulsion properties, and reduced level of residual phytate content. The chosen response parameters are relevant to food, pharmaceutical and cosmetic industries. Improvement in functional properties (emulsion properties) along with reduction in dark colour and toxic phytic acid level is expected to make rapeseed protein safer and commercially more viable for various applications. A multi-objective optimization technique based on Response surface methodology (RSM) has been presented. Using Derringer function, an optimum and feasible experimental condition was obtained with high composite desirability. The calculated regression model proved suitable for the evaluation of extraction process, whose adequacy was confirmed by Anderson-Darling Normality tests, Relative Standard Error of the Estimate (RSEE) and also by means of additional experiments performed at derived feasible experimental condition. The proposed simple alkaline protein extraction process, from defatted partially dephenolized rapeseed meal, under feasible optimal condition, was found to be suitable and potent for the recovery of high-quality vegetable protein. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13197-014-1299-5) contains supplementary material, which is available to authorized users.